Norovirus contamination in the restrooms of markets in Bangkok, Thailand (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Rupprom K, Phumisantiphong U, Wongsuk T, Hirunwong K. 2025. Norovirus contamination in the restrooms of markets in Bangkok, Thailand. Biodiversitas 26: 1406-1413. Norovirus is among the most important causative agents of acute nonbacterial gastroenteritis. The transmission of norovirus can occur through the fecal-oral route, including person-to-person contact and contaminated food, water, and environmental surfaces. This study first investigated norovirus contamination in the restrooms of local markets in Bangkok, Thailand, using Reverse Transcription-quantitative Polymerase Chain Reaction (RT-qPCR) and subsequent semi-nested RT-PCR. An RT-qPCR tested on 211 samples found norovirus GII in 9.5%, GI in 4.3%, and a mix of GI and GII in 1.4% of samples. The urinal flush valves had a higher contamination rate for norovirus than the doorknobs (18.7% vs. 12.5%). Meanwhile, doorknobs had a greater quantity of noroviruses than urinal flush valves (1.68 × 103 ± 3.83 × 103 RNA copies vs. 6.07 × 102 ± 8.71 × 102 RNA copies). Further, the female restrooms and doorknobs were more significantly contaminated with GII than GI (p = 0.048). Using semi-nested RT-PCR, only GII was detected in 31.4% of RT-qPCR-positive samples, and GII.4 was identified as the dominant genotype. Our results revealed a high prevalence of norovirus contamination on frequently touched surfaces in non-outbreak situations. This is significantly beneficial for norovirus outbreak prevention, health risk assessment, and molecular epidemiological investigation of norovirus infection.
Keywords: Bangkok, environmental contamination, market, norovirus, RT-qPCR